Pengaruh Teman Sebaya Dan Kepercayaan Diri Terhadap Aktualisasi Diri Mahasiswa - Ali Rachman; Nina Permatasari (Jurnal Psikologi Pendidikan dan Konseling: Jurnal Kajian Psikologi Pendidikan dan Bimbingan Konseling, 2019)
The purpose of the study was to determine the influence of peers and the belief in self-actualization of Papuan students in class 2018 who studied at ULM Banjarmasin. This research method uses a quantitative approach. Data analysis using multiple regression data analysis by taking into account the analysis test requirements. The results showed that there were influences of peer influence and confidence in self-actualization of students from Papua where the results of the significance calculation were 0,000 < 0,05. The results of data analysis shows that peer influence and trust in self-actualization in Papua students in ULM is 81,3%.